2005
DOI: 10.1038/sj.bjc.6602746
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene insertion/deletion polymorphism is associated with risk of oral precancerous lesion in betel quid chewers

Abstract: To investigate whether angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism is related to the risk of oral precancerous lesions (OPL) in Taiwanese subjects who chew betel quid, a total of 61 betel quid chewers having OPL were compared with 61 asymptomatic betel quid chewers matched for betel quid chewing duration and dosage. The frequency of homozygote for ACE D variant is significantly higher in the case subjects than that of the controls (44.3 vs 24.6%; P ¼ 0.0108). The adjusted odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
15
2
Order By: Relevance
“…To our knowledge, the only study investigating the possible association of the ACE I/D polymorphism with oral oncogenesis has been conducted on Taiwanese betel quid chewers presenting with oral precancerous lesions [10]. Contrary to our findings, the Taiwanese study revealed an increase of the D allele in individuals with oral precancerous lesions in comparison to betel quid chewers with no such lesions [10].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…To our knowledge, the only study investigating the possible association of the ACE I/D polymorphism with oral oncogenesis has been conducted on Taiwanese betel quid chewers presenting with oral precancerous lesions [10]. Contrary to our findings, the Taiwanese study revealed an increase of the D allele in individuals with oral precancerous lesions in comparison to betel quid chewers with no such lesions [10].…”
Section: Discussioncontrasting
confidence: 83%
“…Contrary to our findings, the Taiwanese study revealed an increase of the D allele in individuals with oral precancerous lesions in comparison to betel quid chewers with no such lesions [10]. This conflicting observation may be due either to the relatively small sample of investigated individuals in the Asian study (n 061 in each group) and/or the genetic difference of the two studied populations (Taiwanese against Europeans).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The PCR procedure was described previously. 41 All PCR products were visualized after electrophoresis on 6% polyacrylamide gel with silver nitrate staining.…”
Section: Genotypingmentioning
confidence: 99%